Rekonstruksi Paradigma UMKM Syariah dalam Ekonomi Islam Kontemporer - Budiyono Santoso (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2025)
Contemporary Islamic economics has evolved beyond being merely an alternative to conventional economic systems, positioning itself as a normative–practical paradigm grounded in the principles of tawhid, justice, and maslahah. However, the development of Islamic micro, small, and medium enterprises (MSMEs) remains largely dominated by an instrumentalist approach that emphasizes formal Sharia compliance rather than a comprehensive value-based framework. This study aims to reconstruct the paradigm of Islamic MSMEs by positioning maq??id al-shar?‘ah as the primary ontological, epistemological, and axiological foundation of business practices. Employing a qualitative conceptual research design, this study conducts a systematic literature review of recent publications (2021–2025) from reputable Scopus and SINTA-indexed journals. The findings indicate that maq??id al-shar?‘ah can function integrally to redefine the purpose of Islamic MSMEs, guide ethical and rational business decision-making, and establish multidimensional performance criteria based on fal?? rather than profit maximization alone. As a result, this study proposes an Integrated Conceptual Model of Islamic MSMEs that aligns Islamic values with contemporary economic dynamics, including sustainability, competitiveness, digital transformation, and social inclusion. The model contributes theoretically by shifting Islamic MSME studies toward a paradigmatic approach and practically by providing a value-based framework relevant to national economic policies, particularly within the Indonesian context of Islamic economic development. This study offers a conceptual foundation for future empirical research and policy formulation aimed at strengthening Islamic MSMEs as agents of equitable and sustainable economic transformation.